2020
DOI: 10.1101/2020.02.05.935502
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chemokine Signatures Of Pathogen-Specific T Cells I: Effector T Cells

Abstract: The choreography of complex immune responses, including the priming, differentiation, and modulation of specific effector T cell populations generated in the immediate wake of an acute pathogen challenge, is in part controlled by chemokines, a large family of mostly secreted molecules involved in chemotaxis and other patho/physiological processes. T cells are both responsive to varied chemokine cues and a relevant source for certain chemokines themselves. Yet the actual range, regulation, and role of effector … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(41 citation statements)
references
References 119 publications
7
33
0
Order By: Relevance
“…These results collectively indicate a direct correlation between the strength of TCR signaling and the proportion of chemokine-producing CD8 + T M cells. Furthermore, in vitro “challenge” of OT-I T M cells isolated from Lm- Ova-immunized mice with the SIINFKEL epitope in the presence or absence of broad inhibitors of either translation (cycloheximide) or transcription (Actinomycin D), suggested that most of the CCL3 in Ag- stimulated T M cells was being rapidly transcribed (>60%)(Figure 3D) while only a smaller proportion was stored as mRNA (∼30%) but none as protein, a result also consistent with recent reports (Davenport et al, 2020; Eberlein et al, 2020). Taken together, these data support the hypothesis that IRF4 acts as a transcriptional regulator of chemokine expression downstream of TCR signaling.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…These results collectively indicate a direct correlation between the strength of TCR signaling and the proportion of chemokine-producing CD8 + T M cells. Furthermore, in vitro “challenge” of OT-I T M cells isolated from Lm- Ova-immunized mice with the SIINFKEL epitope in the presence or absence of broad inhibitors of either translation (cycloheximide) or transcription (Actinomycin D), suggested that most of the CCL3 in Ag- stimulated T M cells was being rapidly transcribed (>60%)(Figure 3D) while only a smaller proportion was stored as mRNA (∼30%) but none as protein, a result also consistent with recent reports (Davenport et al, 2020; Eberlein et al, 2020). Taken together, these data support the hypothesis that IRF4 acts as a transcriptional regulator of chemokine expression downstream of TCR signaling.…”
Section: Resultssupporting
confidence: 91%
“…Another important finding in our study relates to the rapid, transcriptionally controlled and coordinated production of CCL3, CCL4 and XCL1 chemokines by CD8 + T M cells induced upon vaccination with both Lm and VSV in response to cognate Ag recognition. These results are consistent with two recent reports that utilized multiple models of acute and chronic infections, as well as ex vivo stimulation assays, and outline that the robust chemokine signature is a key and important feature of both Ag-stimulated effector and memory CD8 + T cells (Davenport et al, 2020; Eberlein et al, 2020). CD8 + T M cells undergoing repetitive in vivo stimulations were also reported to significantly upregulate genes encoding for these chemokines (Wirth et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…Importantly, in the same study, we provide detailed evidence that the induced production of all of the above (CCL1/3/4/5/9/10 and XCL1), but no other chemokines, constitutes a largely invariant functional signature of specific CD8 + and CD4 + T E generated in response to acute viral and bacterial infections, as well as protective immunization (34). Building on this work, we have now extended our investigations to an interrogation of the identities, patterns, regulation, and relevance of chemokines expressed by pathogen-specific T M populations maintained after resolution of acute and under conditions of chronic infections.…”
mentioning
confidence: 53%
“…Other studies, however, have demonstrated a preferential association of constitutively expressed CCL5 with cytolytic granules in HIV-specific CD8 + T cell clones or primary (I˚) human CD8 + T cells (13,31), but murine memory-phenotype CD8 + T cells (CD8 + T MP ), which contain abundant Ccl5 in addition to Ccl3 and Ccl4 transcripts, apparently do not express the corresponding proteins, the synthesis of which requires TCR stimulation (32,33). Our recent work on chemokine signatures of pathogen-specific CD8 + T E may provide clues for a reconciliation of these discrepancies (34): at the peak of the effector response, CD8 + T E express constitutive CCL5 in a subcellular compartment distinct from granzyme (Gzm)-containing cytolytic granules, but upon TCR stimulation, these structures partly coalesce just prior to secretion; in fact, release of prestored CCL5 proceeds so rapidly that temporarily, and within the confines of the immunological synapse, CCL5 concentrations well in excess of 1 mM may be achieved (34), a potential foundation for in vivo CCL5 action at supraphysiological levels (16,17).…”
mentioning
confidence: 99%
See 1 more Smart Citation